Promoting the Rural Non-Farm Sector in Bangladesh : Volume 1. Summary Report - World Bank (Washington, DC, 2013)
The major constraints to RNF growth, according to a large survey of rural entrepreneurs,' include (1) flood and natural disasters; (2) access to electricity; (3) road conditions, (4) access to finance and (5) transportation to markets. Bangladesh's vulnerability to frequent floods and other natural disasters severely hampers operations of more than a third of rural firms. The next most important constraint to RNF growth is the lack of access to electricity, which is available to only 19 percent of rural households (as compared to 31 percent of all households). Third, Bangladesh ranks quite high in terms of road density; however - because of poor construction of roads and bridges, lack of maintenance of roads and waterways, lack of integration of different modes of transportation due to inefficiencies at the container port and in the rail system - road conditions and transportation to markets are reported to be severe problems by 36 and 18 percent of rural firms, respectively. In addition, inadequate access to investment finance and t o working capital disproportionately affects small and medium-sized firms(the "missing middles"). The lack of access to telecommunications adversely affects the start up, growth, and performance of the micro small and medium sized (MSM) firms. As most of the constraints impeding RNF growth relate to the provision of public goods and services, and to macroeconomic and trade policies, the government has a critical role in removing these constraints. Actual actions to remove these constraints have lagged significantly because of the country's lack of: (1) an institutional mechanism to mainstream RNF issues into rural development; and (2) a decentralized local government structure capable of ensuring the efficient delivery of services to rural entrepreneurs. To unleash the growth potential of the RNF sector and create a pro-poor virtuous circle of rural growth, Bangladesh will need to implement the two-pronged strategy of (1) maintaining an enabling rural investment climate, and (2) ensuring an institutional set-up for the efficient delivery of services.